Comparison of Effects of a Herbal Toothpaste with Crest Complete Toothpaste on Streptococcus Mutans and Lactobacillus of Saliva and Plaque Index: A Randomized Clinical Trial - Mina Biria; Seyedeh Saeideh Mohtavipour; Gita Eslami; Alireza Akbarzadeh Baghban (Islamic Dental Association of Iran, 2017)
Background and Aim: In recent years, beneficial effects of herbal hygienic products and toothpastes have significantly been emphasized. This study sought to assess the effects of Masdent toothpaste which contains Pistacia Lentiscus (PL) extract on plaque index and Streptococcus mutans(SM) and Lactobacillus (LB) count in saliva. Materials and Methods: This study was conducted on 60 students aged 18-20 years. Participants were asked to brush their teeth twice a day for four weeks with the assigned toothpaste, Masdent toothpaste which contains PL extract in the case group and Crest toothpaste in the control group. Plaque index was recorded at the onset and end of the study, and salivary samples were taken for SM and LB colony count. Mann-Whitney, independent t- and Wilcoxon tests were used for data analysis. P<0.05 was considered statistically significant. Results: Number of SM and LB colonies significantly decreased in both groups(P<0.01) at the end of the study. However, the difference in SM and LB colonies between the two groups was not significant (PMutans=0.108, PLactobacili=0.796). The reduction in plaque index after using the toothpastes was significant in both groups (P<0.001). This reduction was not statistically different between two groups (P=0.85). Conclusion: Use of herbal toothpaste containing PL extract and Crest toothpaste had similar effects and both significantly decreased SM and LB salivary counts as well as the plaque index.